Chinese English teachers’ occupational intention during distance education: The role of burnout and job-related stress - Zhang, Bo (Frontiers in Psychology, 2022)
Since turnover intention has a negative impact on teachers’ productivity, a bulk of educational research has studied the personal, organizational, and emotional predictors of this construct. Nevertheless, the predictive function of burnout and job-related stress as two emotional factors has been less attended to by scholars. To address this gap, the current empirical study explored the role of burnout and job-related stress in Chinese English teachers’ turnover intention during distance education. In doing so, three pre-designed questionnaires were distributed among 221 Chinese teachers. Having collected the needed data, the researcher analyzed the datasets through the Pearson correlation test and multiple regression analysis. As a result of the correlation test, positive, direct relationships were found between burnout, job-related stress, and teacher turnover intention. Moreover, the results of the regression analysis evinced the significant role of burnout and job-related stress in predicting Chinese English teachers’ turnover intention. The implications of the results are thoroughly discussed.